EFFECT OF SERVICE QUALITY AND PRICE ON CUSTOMER SATISFACTION AT PT. PUTRI MIDAI IN BANGKINANG - Rahmadoni, Restu; Zulher, Zulher; Henrizal, Henrizal (Jurnal Riset Manajemen Indonesia, 2022)
This study aims to determine the quality of service and price on customer satisfaction at PT.Putri Midai in bangkinang. The population in this study are all consumers who have received services by consumers at PT.Putri Midai in Bangkinang using the solvin formula so that 94 consumers can be determined to be samples. Data collection techniques used are questionnaires and interviews. The data analysis technique used is multiple linear regression with a significant level ( 0.05. The results of this study conclude that service quality and price affect customer satisfaction at PT. Putri Midai in bangkinang, with a significance value of less than 0.05. The results of this analysis indicate that service quality and price simultaneously have a significant effect on customer satisfaction at PT. Putri Midai in Bangkinang.